The role of pronouns in achieving textual coherence in the words of Allama Majlisi in the book Al-Mukhtaqkez of Objective Interpretation in Bihar Al-Anwar (A descriptive and analytical study) - Juma , Mushtaq Kazem; Hassanalian, Dr. Somayeh; Daoud, Prof Dr. Imad Jabbar Kazem (Thi Qar Arts Journal, 2023)
The pronouns play an important role in making verbal mechanisms of verbal cohesion in the real linguistic context; because they refer to antecedents or postpositions and this text consists of names or sentences that form a syntactic structure that contributes to the cohesion of meaning in the text; it makes the text have a semantic feature that shows the intention of the text for the listener. If it is true that the pronouns had an important role in explaining the meaning of the signatory’s speech in interpreting verses of the Quran, because his interpretation was rich with compatible and harmonious pronouns with the verses of the Quran that he interpreted and what it includes opinions, meanings and knowledge with verses of the Quran, then his interpretation is a matter of using it as a reference pronoun in accordance with its content and economy for speech, as well as participating in linking descriptive from among reference antecedents (the letter, and alif, and na) and reference postpositions (the pronoun) .